Ethnolinguistic vitality, attitudes and normative pressure as predicors of motivation in learning and speaking Hungarian as second language in Slovenia - Enikő Marton; Nicholas Joyce; László Vincze (Eesti ja Soome-ugri Keeleteaduse Ajakiri, 2014)
The present study examines the motivational context of learning and speaking Hungarian as a second language among the Slovenian-speaking youth in the Dolinsko/ Lendvavidék region of Slovenia. Survey data (N = 119) was collected among secondary school students in 2012 and analysed with path analysis. The results provided considerable support for the proposed model. Findings and implications are discussed, and suggestions for future research are made.